ANALISIS TINGKAT PEMAHAMAN GURU TERHADAP ASESMEN PERKEMBANGAN ANAK USIA DINI PADA TAMAN KANAK-KANAK DI KOTA PONTIANAK - Indriyani, Okii Ayuk (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe level of teacher kindergarten's understanding in developmental assessments is needed as a provision for successful assessment. The purpose of the study is to present a data about the level of teacher's understanding of early childhood development assessment in kindergarten in Pontianak with 48.95% of respondents. Teacher’s understanding in interpreting the procedure is good, with the number 98.96% of respondents. Teacher’s understanding in predicting the procedure is good with the number of 57.29% of respondents. Teacher’s understanding in translating the assessment process is good, with the number of 72.92% of respondents. Teacher’s understanding in interpreting the assessment process is good with 95.833% of respondents. Teacher's understanding in forecasting the assessment process is good, with 97.92% of the respondents. Teacher’s understanding in translating the assessment management is good, with 81.25% of respondents. Teacher’s understanding in interpreting the assessment management is good, with 89.85%. Teacher’s understanding in forecasting on assessment management is good, with 92.708% of respondents. Teacher's understanding in translating the report of assessment results is good, with 33.33% of the respondents. Teacher’s understanding in interpreting the result of the report assessment is good with the number of 72.92% of respondents. Teacher’s understanding in forecasting the report of assessment results is good, with 86.46% of respondents.  Keywords: Level of understanding, Developmental Assessment, Early Childhood Assessment